IDADE DOS CONSELHEIROS DE ADMINISTRAÇÃO E QUALIDADE DA INFORMAÇÃO CONTÁBIL NO BRASIL - Vasconcellos, Edipo Ferreira de (2020)
The main functions of the board of directors are the monitoring and the strategic direction of company executives. The attributes of the board can directly affect the quality of the financial statements. This study investigates the effect of the age of th